The impact of economic policies and globalization on labor income share across advanced and emerging economies: A system GMM estimation - Vallerie Peter; Assis Kamu; Lim, Beatrice Fui Yee; Ho, Chong Mun (Human Resource Management Academic Research Society, 2025)
There has been an increasing interest in research on labor income share trends over the past few decades. Nevertheless, most of the studies only focused on? Advanced and developed countries, leaving a gap in understanding how labor income share behaves in emerging economies. Hence, this paper seeks to contribute to the literature by examining? The determinants of labor income share in a sample of both advanced and emerging economies, focusing on the impacts of taxation, trade, and globalization. This study utilized a System Generalized method of moments (GMM) estimation approach for 57 advanced and emerging economies from 2008 to?2022. The findings indicate that labor income share exhibits strong persistence, reflecting the influence of past income distribution patterns and institutional factors. Moreover,? Trade openness reduces labor income share in advanced economies, whereas the effect in emerging economies is insignificant. In contrast,? Globalization was found to have a significant positive relationship with labor share of income in the full sample, while no significant relationship was found between taxation and labor income share across both economies. Consequently, these findings provide actionable insights for crafting balanced economic policies across different development contexts. Policymakers shall leverage these evidence-based conclusions to design taxation systems and trade frameworks that protect labor income shares while maintaining economic competitiveness, with particular attention to each nation's structural characteristics and development stage.